High-speed railway developments and corporate location decisions. The role of accessibility - Jasper Willigers (European Regional Science Association (ERSA), 2003)
Accessibility is a major factor that determines the effects of transport infrastructure developments on corporate location decisions. High-speed railways have an impact on accessibility by reducing travel times and increasing comfort. However, little research on its effects on location choices has been carried out so far. Still, high-speed railway infrastructure development is advocated for these effects on regional economy. This research uses interviews among corporate decision makers to determine how a change in accessibility due to new high-speed rail infrastructure is perceived by these corporate decision makers and what impact HST infrastructure has on the location choices of firm branches. Firstly, in-dept interviews are held among recently (re)located firm branches to identify accessibility related factors that play a role in the location decision process. For the in-dept interviews we start from the assumption that for firms three aspects of accessibility by passenger transport systems are of importance: access and accessibility for (1) current and potential employees, (2) current and potential business partners, and (3) current and potential customers. Furthermore, corporate decision makers perceive different transport modes in a distinct way. Hereby for example, the level of comfort of the transport mode can be of importance - it might be of more importance for business trips than for commuting. In this paper special attention is given to how the accessibility by high-speed trains is perceived. The perception of the accessibility of a certain place will differ among firms, because distinct firms appreciate the several facets of accessibility differently. This depends on the activities that take place in the firm branch, for example how often face-to-face contact with (international) business partners occurs, and on the cost structure of the firm. An improved accessibility will reduce transport costs, but on the other hand better accessible locations are likely to have higher prices of real estate. Probably for firms a trade off exists between these opposite cost effects, based on their characteristics. But beside these ?objective? factors, subjective properties of accessibility might also be of importance to corporate decision makers. Being settled on good accessible transport hubs can contribute to the firm's image. The interviews shed light on how new high-speed rail infrastructure affects the perception of accessibility by corporate decision makers. By questioning different firm types and sizes it is made clear what types of firms are mostly influenced by this change in accessibility. In a later stage of the research, these factors will be quantified by means of stated preference interviews. The results of these interviews will then be used to improve the way accessibility is embedded in land-use transport interaction models, an important instrument for the ex ante evaluation of transport infrastructure.
Keywords: 330